Which is larger?
A. x n
B. ( x − 1 ) ( ( x n − 1 ) + ( x n − 2 ) + ( x n − 3 ) + ⋯ + ( x 2 ) + ( x 1 ) + ( x 0 ) )
Note:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great solution!
It is extremely helpful to think of this problem in base x . In base x , we have x numbers: 0 through x − 1 . Each power of x is assigned one place. For example, if we had ( 2 ( x 3 ) + ( 4 ( x 2 ) ) + ( 2 ( x 1 ) ) + ( 3 ( x 0 ) ) , in base x it would look like 2 4 2 3 x (assuming that x > 4 ). Note also that x x = 1 0 x , x 0 x = 1 0 0 x , ⋯ . In other words, the x becomes a 0 and gives a 1 to the next higher place.
A. x n = 1 0 0 0 ⋯ 0 0 0 n 0’s x
Rearranging B, we have the following:
( 0 ) ( x n ) + ( x − 1 ) ( x n − 1 ) + ( x − 1 ) ( x n − 2 ) + ( x − 1 ) ( x n − 3 ) + ⋯ + ( x − 1 ) ( x 2 ) + ( x − 1 ) ( x 1 ) + ( x − 1 ) ( x 0 ) .
B. 0 ( x − 1 ) ( x − 1 ) ( x − 1 ) ⋯ ( x − 1 ) ( x − 1 ) ( x − 1 ) n (x-1)’s x
If we add 1 to B, we get:
B = 0 ( x − 1 ) ( x − 1 ) ( x − 1 ) ⋯ ( x − 1 ) ( x − 1 ) ( x ) n of these terms x ⋯ = 0 ( x − 1 ) ( x − 1 ) ( x − 1 ) ⋯ ( x − 1 ) ( x ) ( 0 ) n of these terms x = 0 ( x − 1 ) ( x − 1 ) ( x − 1 ) ⋯ ( x ) ( 0 ) ( 0 ) n of these terms x = 0 ( x ) ( 0 ) ( 0 ) ⋯ ( 0 ) ( 0 ) ( 0 ) n of these terms x = 1 0 0 0 ⋯ 0 0 0 n 0’s x = x n
(Note that each time, the x became a 0 and gave a 1 to the next higher place)
Therefore, A = B + 1 = > A > B
Problem Loading...
Note Loading...
Set Loading...
Consider the expression in B.
( x − 1 ) ( x n − 1 + x n − 2 + ⋯ + x 2 + x + 1 ) = x n − x n − 1 + x n − 1 − x n − 2 + ⋯ + x 2 − x + x − 1 = x n − 1
Thus B will always be smaller than A. We don't even need the restriction that x is a positive integer. Indeed, x need not even be real!
This is a special case of the factorization of difference of n th powers: a n − b n = ( a − b ) ( a n − 1 + a n − 2 b + a n − 3 b 2 + ⋯ + a b n − 2 + b n − 1 ) where a = x and b = 1 .